GAME OF THE NAMES: BRANDING IN SMARTPHONE INDUSTRY - Muzumdar, Prathamesh (Journal of Contemporary Research in Management (JCRM), 2015)
Brand name and product positioning have been a critical issue in the field of branding, especially for the growing market of smartphones. The booming market has made industry to invest more capital in research and development of more sophisticated devices featuring advanced features from basic calling technology to advance computing. Many companies have developed various technologies differentiating themselves from their competitors. The companies are seen following a particular pattern of updating on particular attributes of their products. The purpose of the research study is to understand the preferences of consumers in an experimental item and main item setup. This study explores the fundamental change in preferences along the basic features of a smartphone and change in purchase intentions due to influence of brand title. The study uses paired sample t test, conjoint analysis, and positioning mapping to address the issue of brand influence in experimental item and main item setup. The study uses the Euclidean distance model to explore the dimensions that define particular brands. Overall the study concludes by proving the effect of brand title on preferences and defining the dimensions along which brands are compared.